PENENTUAN KAPASITAS DAN TINGGI MERCU EMBUNG WONOBOYO UNTUK MEMENUHI KEBUTUHAN AIR DI DESA CEMORO - Yanuar Niko Priambodo; Tomy Aziz Susiawan; Sumbogo Pranoto; Suharyanto Suharyanto (Jurnal Karya Teknik Sipil, 2015)
Cemoro village is located in Wonoboyo Sub district , Temanggung District, Central Java Province with the area is 778.9 ha. There are 2.355 people in Cemoro village (1.187 male and 1.168 female). Most of the residents work as plantation farmers. In the dry season, water discharge in the Lingseng River becomes very small, so it can not meet the demand for drinking water and the irrigation needs. Based on water balance, there is a deficit around 27.140,23 m3, that certainly reduce productivity in both agriculture and social welfare. Therefore, the hydraulic structure is needed. To overcome the water deficit one of the efforts is by constructing a small dam. The design minimum capacity of the small dam is 27.140,23 m3. The gross capacity of the storage is 30.653,45 m3 which take into account of sediment storage. Based on correlation graph of elevation, volume storage, and area storage, the head elevation of spillway is +1.542 m. The head elevation of small dam is +1.545,50 m which take into account of flood water level and freeboard. By the presence of small dam, it is expected to cover the water deficit so it can increase the water supply for drinking water and irrigation of horticulture farm.